Introduction and Spread of an Exotic Plant, Spartina alterniflora, Along Coastal Marshes of China - Zhang, Danhua; Hu, Yuanman; Liu, Miao; Chang, Yu; Yan, Xiaolu; Bu, Rencang; Zhao, Dandan; Li, Zheming (Wetlands (Wilmington, N.C.), 2017)
Spartina alterniflora was introduced to China more than 30 years ago, and its arrival corresponded with negative effects on native ecosystems. To elucidate the spatial distribution pattern and spread of S. alterniflora in China, we obtained 400 Landsat image scenes that covered China’s coastal areas since S. alterniflora introduction, and surveyed 40 field sites between 2014 and 2015. A supervised classification method was used to generate the S. alterniflora distribution map along coastal marshes . The results showed that the total distribution of S. alterniflora along China’s coastal areas was 55,181 ha, and ranged between the latitudes19°46′N to 40°47′N. Spartina alterniflora rapidly spread from 1990 to 2003, with an annual expansion rate of 20.4%. However, its area decreased by 12.7% from 2003 to 2005;then the distribution stabilized, and the annual average diffusion rate from 2005 to 2014 was just 4.0%.Overall, S.alterniflora expansion from 1990 to 2014 can be described as a polynomial function. The distribution of S.alterniflora in all provinces except Guangdong Province showed a polynomial increase. At the current expansion rate, S. alterniflora in China could eventually become a dominant plant in most coastal marsh communities in China.